Possibilities of the LMBA in modern radar systems - Gustavsson, Ludwig (My University, 2024)
This master’s thesis was performed in order to examine whether load modulation can be used in order to compensate for systems with reflections due to coupling between elements or poor output match. As these reflections worsen the performance of amplifiers, it is of great interest to mitigate these effects. An example of the implementation of this could be the AESA, where the reflections are dependent of the steering angle of the antenna. The proposed technique for compensation is the load modulated balanced amplifier (LMBA), where a control signal is injected at the isolated port of the second hybrid in a balanced amplifier (BA). In this report, four different topologies for this is assessed, where each uses a different way of injecting the control signal. These topologies are the LMBA, orthogonal LMBA (OLMBA), recursive LMBA (RLMBA) and reflective LMBA (RefLMBA). The load modulating techniques in these topologies are firstly examined by theoretically deriving how each topology is load modulated. This is then verified using non ideal components in the simulation software program Advanced Design Systems (ADS). As a last step, a BA is built with external components in order to verify the operation of the LMBA. The report finds that the theoretical equations for load modulation in an unmatched system shows the same characteristics as the simulation. Both the theory, simulations and measurements shows that the phase of the control signal has to be actively tuned in order to achieve the best load modulating behaviour. However, the load modulation is shown to yield better performance when properly tuned, even outside the bandwidth of the amplifier. This means that while load modulation can be used to compensate for reflections, the technique for which how this is done needs to be refined before it is ready to be implemented.
Keywords: Load modulation, LMBA, OLMBA, RLMBA, RefLMBA, PAE, AESA, Load-pull